Predicting substrate exchange in marine diatom‐heterocystous cyanobacteria symbioses. (28th April 2020) - Nieves‐Morión, Mercedes; Flores, Enrique; Foster, Rachel A.
Summary: In the open ocean, some phytoplankton establish symbiosis with cyanobacteria. Some partnerships involve diatoms as hosts and heterocystous cyanobacteria as symbionts. Heterocysts are specialized cells for nitrogen fixation, and a function of the symbiotic cyanobacteria is to provide the host with nitrogen. However, both partners are photosynthetic and capable of carbon fixation, and the possible metabolites exchanged and mechanisms of transfer are poorly understood. The symbiont cellular location varies from internal to partial to fully external, and this is reflected in the symbiont genome size and content. In order to identify the membrane transporters potentially involved in metabolite exchange, we compare the draft genomes of three differently located symbionts with known transporters mainly from model free‐living heterocystous cyanobacteria. The types and numbers of transporters are directly related to the symbiont cellular location: restricted in the endosymbionts and wider in the external symbiont. Three proposed models of metabolite exchange are suggested which take into account the type of transporters in the symbionts and the influence of their cellular location on the available nutrient pools. These models provide a basis for several hypotheses that given the importance of these symbioses in global N and C budgets, warrant future testing.